The Interplay between Aggression and Resilience in Adolescence: A State-of-the-Art Review - Mustafaraj, Elona; Shkëmbi, Fleura (Research Journal in Psychology and Behavioral Studies, 2025)
The current paper introduces a comprehensive review of the state-of-the-art research on aggression and resilience in adolescence. Through a systematic analysis of recent literature, we examine the conceptual frameworks, prevalence patterns, risk and protective factors, and the complex relationship between these two constructs. Aggression in adolescence, manifesting as both reactive and proactive forms, affects approximately 18% of adolescents and is influenced by factors including executive dysfunction, impulsivity, and environmental exposures. Resilience is conceptualized both as a trait and a dynamic process, serves as a protective and coping mechanism against adversity, and is fostered through individual factors like self-esteem and environmental support. Our analysis reveals a significant negative correlation between aggression and resilience, with mediating factors such as spirituality and self-esteem playing crucial roles in this relationship. The paper also evaluates measurement tools, methodologies, and intervention approaches, highlighting multi-component interventions as particularly effective for enhancing resilience and reducing aggression. We identify critical research gaps, including the need for more longitudinal studies, culturally diverse samples, and integrated intervention approaches. This review contributes to the understanding of how resilience can buffer against aggressive tendencies in adolescents and provides direction for future research and intervention development within such a critical developmental period.